Monitoring of particulate matter concentrations at high altitude ecosystems of Pakistan and China - Zainab, I.; Ali, Z.; Ahmad, M. S.; Zona, Z.; Raza, S. T.; Sidra, S.; Nasir, Zaheer A.; Colbeck, Ian; Liu, W. (Pakistan Agricultural Scientists Forum, 2015)
Particulate matter exhibits different behavior with altitude. A comparative analysis was carried out to monitor PM1, PM2.5, PM4, PM10and PMTotal at elevations above 3000 m in both China and Pakistan. Real time monitoring of PM was carried out at both sites using a DustTrak DRX (model 8533, TSI Inc.) for 24 hours each. In Pakistan, the average value of PMTotal was 415+ 16 µg/m³ while in China the value was considerably lower i.e. 110+ 57 µg/m³. The 24-hour mean values recorded were well above the WHO recommended limit of 25 µg/m³. These results indicate that, even at sites some distance from anthropogenic sources, PM concentrations still pose a health risk.
Keywords: fine particulate matter; high altitude; China; Pakistan